Kepastian Hukum Dalam Menghadapi Faktor Penghambat Iklim Investasi Indonesia Pasca Reformasi Undang-Undang Cipta Kerja - Sumeirat Tresna Rahayu (Jurnal Dialektika Hukum, 2026)
This study examines the issue of legal certainty in Indonesia’s investment climate following the enactment of Law No. 6 of 2023 on Job Creation. Although Indonesia possesses significant investment potential, various obstacles, such as overlapping regulations, policy disharmony between the central and local governments, and inconsistencies in law enforcement, continue to generate uncertainty for investors. The study aims to analyze investment barriers from the perspective of Gustav Radbruch’s concept of legal certainty, identify forms of legal uncertainty following the reform, and formulate appropriate legal strategies. The method employed is a normative legal approach with a descriptive-analytical framework based on a literature review. The findings demonstrate that the reforms introduced by the Job Creation Law have not yet fully resolved legal uncertainty, particularly in terms of implementation and institutional coordination. Therefore, a reconstruction of legal strategies is required through regulatory harmonization, strengthening the integration of the licensing system, and enhancing the consistency of law enforcement to foster a more certain and equitable investment climate.